The effects of trypanosomiasis and other factors on rectal temperature and blood picture of Muturu cattle (Bos brachyceros) reared under traditional village management system - Uzu, D.V.; Umunna, N.N.; Bawa, E.K. (1998)
Blood samples were collected during the rainy and dry season months from a total of 247 traditionally village managed Muturu cattle randomly selected from five Local Government Areas (LGAs) of Benue State, Nigeria. The blood samples were examined for the presence of Trypanosome organism through parasitologic and Antibody-detection ELISA (Ab'ELISA) techniques as well as analysed for haemoglobin (Hb), packed cell volume (PCV), Total Protein (TP), Magnesium (Mg), Calcium (Ca) and Phosphorus (P). The results of the Ab'ELISA showed a higher prevalence rate of trypanosomosis (66.8 percent than the conventional parasitological techniques (8.9 percent). The Ab'ELISA also discriminated between infected and non-infected cattle and differentiated between the different Trypanosoma species in cases of mixed infections. The results of the study suggested the Ab'ELISA as being a useful technique for epidemiological assessment of bovine trypanosomiasis in Nigeria than the conventional parasitological techniques. Inspite of the high prevalence rate (66.8 percent) of trypanosomiasis in Muturu cattle as detected through Ab'ELISA technique, the infected and non-infected animals maintained normal rectal temperature, Hb concentrations, PCV, serum Mg. Ca and P; an indication of their trypanotolerant nature. Serum TP in both infected and non-infected animals however, remained consistently low probably due to the low crude-protein of the native grasses and crop residues which were the main feed resources of the animals. Rainy season levels of Hb, PCV, TP and Ca in the Muturu were significantly (P<0.001) higher than those in the dry season. While age had no effect on rectal temperature and the blood picture of the Muturu, serum TP were significantly (P<0.001) higher in the female than their male counterpart. The endemic nature of Trypanosomiasis in Benue State suggests the need for further investigation into the effects of the disease in the Muturu through studies on productivity parameters and male reproductive system.